Macroinvertebrados del suelo en cuatro unidades agroecológicas de cacao (Theobroma cacao L.) en la región San Martín - Torres Panduro, Samy Carolina (2015)
The Amazon is one of the most complex ecosystems on earth, where it is interrelated the flora, fauna (macro and micro), soil, water and air, maintaining a balanced environment, through the fertility of the soil. That is why this work has been done with the aim to determine the density, biomass and distribution of the macroinvertebrates of the soil in plantations of cacao (Theobroma cacao L.), in two sessions (dry and rainy season). We selected four different agro-ecological units (CHI, SLD, MET and CMP). Where it used the methodology Tropical Soil Biology and Fertility (TSBF), ranked five sampling points along a separated from 10 m. In each one of them was placed a frame of 25 x 25 cm. getting a pit and/with layers of leaf litter, 0-10 cm. 10-20 cm and 20-30 cm. The entomology laboratory of the Research Institute of the Peruvian Amazon identified and preserved the samples obtained in the field. There was a total density of 20 649 ind/m2, in dry period 13 847 ind/m2 and in rainy period 6802 ind/m2. In both periods the higher density is presented in SLD, with 5 792 ind/m2 in dry period and 4 110 ind/m2 in rainy season. Represented in its majority by Haplotaxiada, Isoptera and Hymenoptera. The whole biomass was about 405, 24 g/m2, in dry period 51, 81 g/m2 and in rainy period 353, 43 g/m2, with CMP presented the highest biomass, with 189.94 g/m2 and SLD with less biomass 14.59 g/m2, represented in its majority by Haplotaxiada and Diplopoda. In the vertical distribution, the results show increased density in the stratum of 0-10 cm with 14 239 ind/m2 and in the vertical distribution of biomass also shows, that the stratum of 0-10 cm is more representative with 371.82 g/m2. The results show the higher density in the agroecological SLD unit and higher biomass to SLD; it also shows that the stratum of 0-10cm distributed mainly the macroinvertebrates.